Analysis of the expression of micrornas and their targets in developing inflorescences of oil palm (Elaeis guineensis Jacq.) / Ho Hui Li - Ho , Hui Li (2018)
African oil palm (Elaeis guineensis Jacq.) is an important perennial oil crop with a long flower developmental phase. The formation of oil palm fruits relies on the successful progression of upstream flower developmental events in the inflorescences. As a monoecious plant, the sex ratio of the female to male inflorescences on each palm is important for breeding and commercial production. This study examined the gene expression profiles at the small RNA transcriptome level in developing female and male inflorescences of oil palm at the +6 and +15 stages of floral development, which correspond to the emergence of floral meristems and to the formation of floral organs respectively. This study also aimed to determine the differences in the mRNA transcriptome between the female and male inflorescences. As only the fertilized female inflorescences develop into fruit bunches, an integration of high-throughput sequencing of mRNA, small RNA and RNA degradome libraries was used to identify and to quantify miRNAs and their mRNA targets that were differentially expressed in +6 and +15 female inflorescences. From the female inflorescences, a consensus reference transcriptome was assembled. Mononucleotide repeats constituted the largest group of simple sequence repeats in the current datasets, followed by tri- and dinucleotide repeats. From the transcriptome data, 97 potential sex-specific transcripts were identified. Transcript expression patterns were validated using nCounter analysis for oil palm orthologs of acid phosphatase and DEFICIENS, which showed male-specific expression patterns whereas orthologs of bZIP transcription factor, late embryogenesis abundant protein and TASSELSEED1 showed female-specific expression patterns. Transcripts for orthologs of acid phosphatase and late embryogenesis abundant protein were also strongly inflorescence-specific. Twenty-nine putative oil palm-specific miRNAs were identified and different subsets of orthologous miRNA were expressed in female and male inflorescences, with miR535 as the most highly expressed miRNA in the female inflorescence while miR166 was the most highly expressed miRNA in the male inflorescence. From the 18 orthologous miRNA families and their mRNA targets with differential expression between +6 and +15 female inflorescences, two distinct subsets of orthologous miRNAs showed inverse expression patterns in +6 and +15 female inflorescences: miR163, miR168, miR172, miR1859, miR1873, miR396, miR4365, miR835 and miR858 showed an inverse expression pattern to at least one of their predicted targets and cleavage products of some of these predicted targets were identified in the degradome libraries. Many of the predicted targets are transcripts encoding protein kinases and components involved in DNA replication and repair. In summary, the present study showed that distinct subsets of miRNAs were differentially expressed in developing female and male inflorescences of oil palm. The inflorescence- and sex-specific transcripts for which the expression coincides with the early phase of sex differentiation in oil palm inflorescences may account at least in part, for the differences between female and male inflorescences. The miRNAs that were differentially expressed in the +6 and +15 female inflorescences are likely to act in concert with their mRNA targets to regulate the early phase of floral organ establishment.